2009
DOI: 10.1242/dev.027748
|View full text |Cite
|
Sign up to set email alerts
|

Sall genes regulate region-specific morphogenesis in the mouse limb by modulating Hox activities

Abstract: The genetic mechanisms that regulate the complex morphogenesis of generating cartilage elements in correct positions with precise shapes during organogenesis, fundamental issues in developmental biology, are still not well understood. By focusing on the developing mouse limb, we confirm the importance of transcription factors encoded by the Sall gene family in proper limb morphogenesis, and further show that they have overlapping activities in regulating regional morphogenesis in the autopod. Sall1/Sall3 doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 79 publications
2
48
0
Order By: Relevance
“…SALL4 can heterodimerize with other family members such as SALL1 (Sakaki-Yumoto et al, 2006) and Sall1, Sall2, and Sall3 have essential redundant functions during murine neurulation (Bohm et al, 2008). Sall1 and Sall3 are involved in Shh linked A/P patterning of developing mouse limbs (Kawakami et al, 2009) and human Sall1 mutations produce TownesBrocks Syndrome, most likely caused by the dominant-negative effect of truncated SALL1, which includes among its defects thumb abnormalities (Kohlhase et al, 1998;de Celis and Barrio, 2009). Functional gene knockout studies of mouse autopod development showed that Sall1 and Sall3 are partially redundant.…”
Section: Comparison Of Sall1 Sall3 and Sall4 Expression During Limbmentioning
confidence: 99%
“…SALL4 can heterodimerize with other family members such as SALL1 (Sakaki-Yumoto et al, 2006) and Sall1, Sall2, and Sall3 have essential redundant functions during murine neurulation (Bohm et al, 2008). Sall1 and Sall3 are involved in Shh linked A/P patterning of developing mouse limbs (Kawakami et al, 2009) and human Sall1 mutations produce TownesBrocks Syndrome, most likely caused by the dominant-negative effect of truncated SALL1, which includes among its defects thumb abnormalities (Kohlhase et al, 1998;de Celis and Barrio, 2009). Functional gene knockout studies of mouse autopod development showed that Sall1 and Sall3 are partially redundant.…”
Section: Comparison Of Sall1 Sall3 and Sall4 Expression During Limbmentioning
confidence: 99%
“…They play diverse roles in embryonic development, including the development of limbs (12,13). Among four Sall genes in mammals, Sall4 is a key regulator of stemness in stem cells and progenitor cells, such as embryonic stem cells, induced pluripotent stem cells, spermatogenial progenitor cells and cancer cells (14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Hoxa13-misexpressed cells are sorted out from Hoxa13-negative cells (Yokouchi et al, 1995). In addition, Hox13 paralogue genes coordinately regulate the expression of the cell surface receptor, EphA, during limb development (Stadler et al, 2001;Cobb and Duboule, 2005;Salsi and Zappavigna, 2006;Kawakami et al, 2009). Interactions of Eph receptors with their ephrin ligands lead to cellular recognition and subsequent cell repulsion.…”
Section: Molecular Basis Of Positiondependent Cell Adhesivenessmentioning
confidence: 99%
“…In addition to EphA4, other EphA receptors, such as EphA3 and EphA7, are also expressed in the distal region of mouse limb bud (Stadler et al, 2001;Cobb and Duboule, 2005;Kawakami et al, 2009). EphA7 is expressed in the distal region of the limb bud, and restricted to presumptive digits.…”
Section: Cell Surface Moleculesmentioning
confidence: 99%